Comparative evaluation of sclerostin levels in gingival crevicular fluid in the treatment of chronic periodontitis patients using diode laser as an adjunct to scaling and root planing: A clinico-biochemical study - B S Jagadish Pai; Nithya R Krishnan; Amit Walveker; Sreedevi Keeneri; Ansu Emmanuel; Neethi R Krishnan; Menezes Anosca Lira (Wolters Kluwer Medknow Publications, 2021)
Aims: Sclerostin is an inhibitor of bone formation, and laser irradiation enhances osteoblast proliferation. The objective of this study was to assess and compare the gingival crevicular fluid (GCF) sclerostin level and clinical parameters of chronic periodontitis patients following the application of diode laser (810 nm) as an adjunct to scaling and root planing (SRP). Subjects and Methods: Fifteen systemically healthy chronic periodontitis patients (age 35-55 years) with probing pocket depth ≥5mm were included in this split-mouth study. SRP and pocket irradiation with diode laser were done in the test group and SRP alone in the control group at baseline. Low-level laser therapy application and saline irrigation were done in both the groups, respectively, in the 2nd and 3rd visits. Two microliters of GCF samples was collected from both the groups at baseline before treatment and on the 90th day for the assessment of sclerostin concentration. Results: This study showed a statistically significant reduction of clinical parameters in the test and control groups at the end of 3 months. Both the groups showed a statistically significant reduction of sclerostin levels in GCF after 3 months, in which the test group (125.80 ± 28.21 to 82.80 ± 9.31) showed a highly significant reduction (P = 0.000). Conclusions: The adjunctive use of laser had shown a beneficial effect in terms of clinical parameters and osteoblast proliferation by the reduction in the levels of sclerostin in GCF. From the observations of this study, it can be concluded that the therapeutic effectiveness of diode laser as an adjunct to SRP is having a beneficial effect and sclerostin can be used as a potent biomarker.